Density functional theory study on hydrogen storage capacity of metal-embedded penta-octa-graphene. (5th September 2022) - Bi, Lan; Miao, Zhicheng; Ge, Yan; Liu, Ziyi; Xu, Yi; Yin, Jie; Huang, Xin; Wang, Yunhui; Yang, Zhihong
Abstract: H2 storage capabilities of penta-octa-graphene (POG) adorned by lightweight alkali metals (Li, Na, K), alkali earth metals (Be, Mg, Ca) and transition metals (Sc, Ti, V, Cr, Mn) are studied by density functional theory. Metals considered, with the exception of Be and Mg, can be stably adsorbed to POG, effectively avoiding metal clustering. The average H2 adsorption energies are calculated in a range from 0.14 to 0.95 eV for Li (Na, K, Ca, Sc, Ti, V, Cr, Mn) decorated POG. Because the H2 adsorption energies for reversible physical adsorption lie in the range of 0.15–0.60 eV and the desorption temperatures fall in the range of 233–333 K under the delivery pressure, 4Li@POG and 2Ti@POG are found to be the most suitable for H2 storage at ambient temperature. By polarization and hybridization mechanisms, up to 3 and 5 hydrogen molecules are stably adsorbed around each Li and Ti, respectively. The H2 gravimetric densities can reach up to 9.9 wt% and 6.5 wt% for Li and Ti decorated POG, respectively. Our findings suggest that, with metal decoration, such a novel two-dimensional carbon-based structure could be a promising medium for H2 storage. Graphical abstract: Image 1 Highlights: The H2 novel storage capacities of POG decorated by AMs, AEMs and TMs were studied. Li (Na, K, Ca, Sc, Ti, V, Cr, Mn)-decoration improve hydrogen adsorption. Li (Na, K, Ca, Sc, Ti, V, Cr, Mn) can disperse stably on POG proved by DFT and MD. By polarization and hybridization, E ads (H2 ) was in a range from 0.14 to 0.95 eV. HGDs are 9.9 wt% and 6.5 wt% for Li and Ti decorated POG, respectively.